(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This paper demonstrate how effectively teach kids to Phonetics. With the help of art therapy- pictures, songs, and images kids will learn new words in L2, and by singing a song it will be easier to pronounce correctly the words in L2. The paper shows the methods of teaching Phonetics, Phonology, Morphology and three topics are chosen that are related to them, such as Sounds, Phonological awareness, Morphemes. This paper illustrates the visuals which will be useful in teaching process.